Mejilawi to Enhance the Symbolic Thinking Abilities for Children’s Kindergarten - Siti Kusnul Khotimah; Dian Kristina; Muhammad Azzam Muttaqin (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2023)
This research aims to improve children's symbolic thinking abilities through the use of mejilawi (teaching method) and describes the application of mejilawi in enhancing children's symbolic thinking abilities. The subjects of this research were Group A students of PAS Baitul Qur'an Gontor Full-day Kindergarten. This research uses a qualitative descriptive classroom action research approach. Data collection methods used in this research include observation and oral tests. Meanwhile, the data analysis method uses a qualitative descriptive approach. The research model used in this research refers to Kemmis and McTaggart's theory, which is applied in a spiral form consisting of planning, implementation, observation and reflection. Research findings show increased children's symbolic thinking abilities after implementing mejilawi. In cycle I, out of 20 children aged 4-5 years at PAS Baitul Qur'an Gontor Fullday Kindergarten, 11 (55%) achieved BSH and BSB grades. In cycle II, there was an increase in the number of children who obtained BSH and BSB scores, reaching 17 (85%). The application of mejilawi as a learning medium to improve children's symbolic thinking skills consists of five stages: (1) the child arranges ten bowls neatly and counts them, (2) the child arranges and places the numbers 1 to 10 under the bowl, (3) the child holds the nuts correctly, (4) children put nuts in their hands as a symbolic representation of the numbers, (5) children are allowed to count the number of nuts again in each bowl. Scientific use of mejilawi can improve children's symbolic thinking abilities.